Management of the organizational culture of the public service of the Republic of Kazakhstan - Abdrakhmanova, A. ("M. Narikbayev KAZGUU University". Nur-Sultan, 2021)
This study is devoted to the study of "Management of the organizational culture of the civil service of the Republic of Kazakhstan", the akimat of the Esil district of the city of Nur-Sultan was chosen as the object. The process of reforming the civil service of the Republic of Kazakhstan in recent years has been characterized by increased attention to the issues of organizational changes, personnel management of state bodies. For more than twenty years of independence, the Institute of Public Service of the Republic has passed several stages of development, and this work continues to this day, including in the framework of the development of the organizational culture of state organizations. The task of the civil service of the country is to move from a bureaucratic, hierarchical, inefficient organizational culture to a productive, positive, strong organizational culture focused on the needs of citizens, the quality of public services, in general, in order to obtain the proper status and image of the civil service in the republic and abroad. Our task is to conduct a survey among the employees of the akimat and identify at what level the organizational culture actually is.
Keywords: organizational culture, civil service, civil service value, assessment of the activities of the civil service